Fixed Asset Management of Pondok Pesantren: Practices, Practitioners, and Praxis - Mu'afi, M. Hanief; Sugiri, Slamet (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2025)
This study investigates fixed asset management practices in Islamic boarding schools (pesantren) through the lens of strategy-as-practice theory, with particular attention to the dimensions of practice, practitioner, and praxis. Employing a qualitative case study design, the research explores two contrasting pesantren: Pondok Tahfizh Daarul Qur’an (modern typology) and Pondok Pesantren BUQ (traditional salaf typology). Data were collected through in-depth interviews, institutional document analysis, and NVivo-assisted thematic coding. The findings reveal distinct patterns of asset ownership, regulation, maintenance, and reporting. Daarul Qur’an demonstrates formalized asset management mechanisms under foundation governance, though hindered by limited human resource competencies and procedural inconsistencies. In contrast, BUQ maintains a highly personalized, non-bureaucratic model rooted in kiai leadership, with minimal documentation and planning. The praxis of asset management is shaped not only by structural governance but also by the interplay of pesantren culture, practitioner agency, and socio-religious values. This study offers empirical insights into the organizational behaviors that facilitate or impede strategic asset management in Islamic education contexts. Limitations include the narrow case scope and typological selection, suggesting the need for future research across broader pesantren variants. Recommendations include the development of culturally grounded yet standardized asset management guidelines and capacity-building initiatives to professionalize resource governance in pesantren settings.